2016
DOI: 10.18632/oncotarget.6903
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation and activation of YAP by hypoxia contributes to the chemoresistance of SN38 in hepatocellular carcinoma cells

Abstract: Although hypoxia is a prominent feature contributing to the therapeutic resistance of hepatocellular carcinoma cells (HCC) against chemotherapeutic agents, including the Topoisomerase I inhibitor SN38, the underlying mechanism is not fully understood and its understanding remains a major clinical challenge. In the present study, we found that hypoxia-induced nuclear translocation and accumulation of YAP acted as a survival input to promote resistance to SN38 in HCC. The induction of YAP by hypoxia was not medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 55 publications
6
62
1
Order By: Relevance
“…Dai et al also showed that HIF-1α did not mediate hypoxia-triggered YAP nuclear translocation [17]. However, in the present study, LATS1 and p-LATS1 (Ser909) expression levels were decreased under hypoxia.…”
Section: Discussioncontrasting
confidence: 72%
“…Dai et al also showed that HIF-1α did not mediate hypoxia-triggered YAP nuclear translocation [17]. However, in the present study, LATS1 and p-LATS1 (Ser909) expression levels were decreased under hypoxia.…”
Section: Discussioncontrasting
confidence: 72%
“…The activation of YAP promotes survival, chemoresistance, metastasis, and the other malignant properties of HCC [43] . It has been reported in recent studies that hypoxia induces nuclear translocation and activation of YAP in a HIF-independent way, and the subsequent activation of target genes promotes cell survival, resistance to SN38 and sorafenib in HCC [17,43] . Meanwhile, statins (the inhibitors of hydroxymethylglutaryl-CoA reductase) can suppress YAP target genes and overcome hypoxia-induced resistance to sorafenib [43] .…”
Section: Hippo-yap Pathwaysmentioning
confidence: 99%
“…Yet recently, the findings on the HIFs-independent regulation of tumor angiogenesis and chemoresistance under hypoxic conditions have challenged this notion and raised the possibility that the other important signaling pathways may also participate and promote the progression and malignance of HCC [10][11][12][13][14] . Accumulating evidence shows that Yes associate-Protein (YAP) [17] , matrix metalloproteinases (MMPs), high mobility group box 1 (HMGB1) and glucose metabolism enzymes are involved in hypoxiamediated effects in HCC [18] . The above key molecules would be activated as sensors of intratumoral oxygen tension, and trigger the subsequent activation of hypoxia-mediated process, thus may also be regarded as potential targets for HCC therapy.…”
Section: Molecular Pathways Involved In Hypoxic Hcc Malignancementioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide (1). Although great progress has been achieved in the diagnosis and treatment of HCC, the overall survival of HCC patients remains poor (2). Alteration of metabolism is a hallmark of cancer cells (3).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the oncogenic roles of the MVA pathway in tumorigenesis (6,7). It has been reported that enzymes involved in the MVA pathway were upregulated in breast cancer and HMGCR promoted the transformation of benign breast epithelium (2). In gastric cancer cells, HMGCR has been reported to activate the hedgehog signaling pathway and promotes the growth and migration of cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%